Seepage starting pressure gradient of leaching solution under microscopic pore structure evolution of uranium-bearing sandstone by acid in situ leaching - Song, Jiayin; Sun, Bing; Zeng, Sheng; Li, Da; Cai, Qiue; Zhang, Xuan; Chen, Xinge (Physics of fluids (1994), 2025)
To investigate the influence of pore structure evolution under physicochemical reaction stimulation on the variation of seepage pressure gradient in percolation systems. The study conducted seepage experiments under three different flow rates, employing computed tomography scanning to characterize sandstone samples during leaching. The relationship between pressure gradient and migration capacity of the leaching solution was established through the pore radius and fractal dimension obtained after three-dimensional reconstruction. The results indicated that minerals in sandstone were continuously dissolved and eroded during leaching, and the number of pores and throats increased with the leaching time. The pores were predominantly sub-nanoscale pores with a small proportion of micrometer-scale pores, while the throats mainly consisted of sub-nanoscale and nanoscale throats. The proportions of micrometer-scale pores, sub-nanoscale pores, and nanoscale pores were different under different flow rates, while throat channel distributions within the same range differed. Sandstone exhibited more effective leaching at flow rate of 0.8 ml/min, with the number of pores and throats increasing and the radius also expanding over time. Furthermore, the pore fractal dimension (Df) of sandstone increased with permeability enhancement, whereas the tortuosity fractal dimension (Dt) decreased with permeability increase. Based on reconstructed pore parameters, a predictive model correlating pressure gradient with mobility coefficient of leaching solution was established using mechanical equilibrium and fractal theory, demonstrating satisfactory model performance. The research provided a theoretical foundation for real-time adjustment of injection pressure based on pressure gradient monitoring when encountering pore clogging during leaching, offering significant practical implications for improving leaching efficiency.